London's waterfront 1100-1666 : excavations in Thames Street, London, 1974-84 /: excavations in Thames Street, London, 1974-84. (2018) - Schofield, John, 1948-; Blackmore, Lyn; Pearce, Jacqueline, 1955-; Dyson, Tony
No abstract available